A STUDY OF EFL STUDENTS’ ORAL COMMUNICATION STRATEGIES IN DISCUSSIONS - Rosi Hardianti (Indonesian EFL Journal, 2016)
: In the process of communication, EFL students frequently experience problem in saying what they want to say in English. Oral Communication Strategies (OCS) surface as the students needs to solve problems of expressing their intended meaning. This descriptive qualitative study intended to analyze (1) types of OCS used by students while conducting discussion, and (2) the students’ reasons for using certain types of OCS. The participants of this study were a group discussion consisting of five EFL students of English Education Department in the University of Kuningan. The data in this study were gained from observation and interview which were then transcribed. The data were analyzed qualitatively by using Dornyei’s (1995) taxonomy of OCS. The results revealed that students participated in this study tended to use achievement strategies (73.07%) more frequently than avoidance strategies (26.92%). Specifically, students used nine out of twelve communication strategy types, and the most frequent strategy used by students while conducting discussion was the use of fillers strategy (51.28%). Then, the students’ reasons for using fillers strategy in their communication were basically because of their lack of English vocabulary knowledge and content knowledge of topics which were being discussed. Thus, students encounter communication problems as the results of target linguistic inadequacy. Hence, further study might yield different result if the topics chosen for discussion were desired topics among students.Keywords: EFL (English as a Foreign Language), Oral Communication Strategies, Discussion